Red Cell Distribution Width as a Predictor of Severity of Acute Pancreatitis - Thapa, Pradip; Gautam, Subodh; Pun, Hemanta; Sharma, Anup (Journal of Nepalgunj Medical College, 2019)
Introduction: Acute pancreatitis (AP) is a disorder featured by local and systemic inflammatory response, which manifests as mild, self-limited disorder to severe and sometimes fatal disease. Red cell distribution width (RDW) is reflective of systemic inflammation and has been shown to be effective at predicting severity. This study was aimed to investigate the association between Red cell distribution width as coefficient of variation (RDW -CV) on admission and severity of acute pancreatitis.Method: This was a hospital based prospective study conducted in the Department of Surgery, Nepalgunj Medical College Teaching Hospital for a period of 2 years from July 2017 to June 2019. The patients with acute pancreatitis were categorized into mild, moderate and severe acute pancreatitis. The value of RDW-CV on admission was correlated with the severity of acute pancreatitis.Results: RDW-CV on admission was significantly correlated with the severity of AP (p value